The Genetic Link between Parkinson’s Disease and the Kynurenine Pathway Is Still Missing - Nóra Török; Rita Török; Zoltán Szolnoki; Ferenc Somogyvári; Péter Klivényi; László Vécsei (Parkinson's Disease)
Background. There is substantial evidence that the kynurenine pathway (KP) plays a role in the normal physiology of the brain and is involved in the pathology of neurodegenerative disorders such as Huntington’s disease and Parkinson’s disease (PD). Objective. We set out to investigate the potential roles in PD of single nucleotide polymorphisms (SNPs) from one of the key enzymes of the KP, kynurenine 3-monooxygenase (KMO). Methods. 105 unrelated, clinically definitive PD patients and 131 healthy controls were enrolled to investigate the possible effects of the different alleles of KMO. Fluorescently labeled TaqMan probes were used for allele discrimination. Results. None of the four investigated SNPs proved to be associated with PD or influenced the age at onset of the disease. Conclusions. The genetic link between the KP and PD is still missing. The investigated SNPs presumably do not appear to influence the function of KMO and probably do not contain binding sites for regulatory proteins of relevance in PD. This is the first study to assess the genetic background behind the biochemical alterations of the kynurenine pathway in PD, directing the attention to this previously unexamined field.